2017
DOI: 10.1007/s12975-017-0537-3
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of Acute Stroke Etiology (BASE) Study Methodology

Abstract: Acute ischemic stroke affects over 800,000 US adults annually, with hundreds of thousands more experiencing a transient ischemic attack. Emergent evaluation, prompt acute treatment, and identification of stroke or TIA (transient ischemic attack) etiology for specific secondary prevention are critical for decreasing further morbidity and mortality of cerebrovascular disease. The Biomarkers of Acute Stroke Etiology (BASE) study is a multicenter observational study to identify serum markers defining the etiology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…Confounders affect the signal-to-noise ratio and thus the sensitivity, specificity, and predictive value of the biomarker [7,8]. It is more likely that multiple biomarkers or panels from "Big Data" could improve precision [8,[12][13][14][15][16]. Big Data in stroke effectively aids in the identification of relevant biomarkers from the myriad possibilities [17].…”
Section: Challenges In Biomarker Utilizationmentioning
confidence: 99%
“…Confounders affect the signal-to-noise ratio and thus the sensitivity, specificity, and predictive value of the biomarker [7,8]. It is more likely that multiple biomarkers or panels from "Big Data" could improve precision [8,[12][13][14][15][16]. Big Data in stroke effectively aids in the identification of relevant biomarkers from the myriad possibilities [17].…”
Section: Challenges In Biomarker Utilizationmentioning
confidence: 99%
“…Therefore, there is an increasing need for biomarkers capable of identifying stroke etiology in clinical practice. In recent years, numerous studies have investigated a large amount of new blood biomarkers in relation with stroke etiology [3][4][5][6][7]. However, low sensitivity and specificity of the target biomarkers difficult their translation into clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…Many other brain-specific proteins studied have similar limitations (Ahmad et al, 2012; Fassbender et al, 1997; Kövesdi et al, 2010; Wunderlich et al, 2006), while proteins such as copeptin found elevated under acute stroke conditions are highly non-specific for the brain and may serve as a more general marker of physiologic stress (Katan et al, 2009; Nickel et al, 2012). Another promising approach is utilization of blood gene expression analysis to identify the etiology of acute ischemic stroke (Jauch et al, 2017). However, the timing of RNA expression that requires blood collection 24 hours after stroke onset (Jauch et al, 2017) may add limitations to this approach to meet “the ideal ischemic stroke biomarker” requirements.…”
Section: Introductionmentioning
confidence: 99%
“…Another promising approach is utilization of blood gene expression analysis to identify the etiology of acute ischemic stroke (Jauch et al, 2017). However, the timing of RNA expression that requires blood collection 24 hours after stroke onset (Jauch et al, 2017) may add limitations to this approach to meet “the ideal ischemic stroke biomarker” requirements.…”
Section: Introductionmentioning
confidence: 99%